Perkawinan beda agama dalam perspektif hukum Islam dan peraturan perundang-undangan di Indonesia - Ubaidillah, Hasan; Al-Masri, Nurhan (AS-SAKINAH, 2025)
This study aims to examine the clarity of the legal status of interfaith couples in the perspective of Islamic law and national law in Indonesia, and analyze the normative conflicts that arise between the two. The approach used is a normative juridical approach with data collection techniques in the form of literature study of legislation, religious fatwas, and relevant scientific literature. The results show that national law through Law Number 1 Year 1974 does not explicitly regulate the legality of interfaith marriages, giving rise to legal uncertainty. Meanwhile, the majority of Islamic law rejects this practice because it is considered contrary to the values of sharia. The conflict between the two creates a legal dilemma that affects the marital status and civil rights of the couple and the children born. This research recommends the importance of harmonization between religious and state law through regulatory reform and increased dialogue between state institutions and religious authorities to create a more just and inclusive legal system.